Assembly of the photosynthesis apparatus - Hoober, J. Kenneth (Henry Stewart Talks, 2007)
Biology of chloroplast development including biogenesis of the thylakoid membrane system, Binding of chlorophylls to proteins determined by Lewis acid strength of the Mg, Requirement for synthesis of chlorophyllide b on the inner membrane of the chloroplast envelope for import of apoproteins of light-harvesting complexes, State transitions as a probe of thylakoid differentiation, Initiation of thylakoid membrane assembly on the chloroplast envelope inner membrane
Reviewed at 2022/04/12